Uterine Rupture in Subsequent Pregnancy in a Patient with Previous Uterine Manipulator Associated Uterine Perforation - ihsan Bagli; Yasemin Dogan; Selcuk Erkilinc; Ali Emre Tahaoglu (Medical Network, 2019)
To report a case who experienced uterine rupture at 38th week of gestation and had a history of manipulator associated uterine rupture. A 25 years old primigravid woman at 38 weeks of gestation was referred to our hospital with the signs of active labor. Heavy lower abdominal cramps and signs of acute abdomen suggested uterine rupture and emergent cesarean section was performed. A 3 cm in size and circular in shape uterin rupture at the fundus that was imitative of enlarged previous manipulator associated rupture was observed. A manipulator associated uterine rupture should be repaired when encountered in reproductive ages in order to prevent a possible uterine perforation during subsequent pregnancy.